2015
DOI: 10.1007/s11368-015-1222-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of technosol and biochar amendments combined with Brassica juncea L. on the fractionation of Cu, Ni, Pb and Zn in a polluted mine soil

Abstract: Purpose Soil metal pollution is a widespread problem around the world and remediation of these soils is difficult. The objective of this study was to investigate the effect of two different strategies on the chemical fractions of metals in a soil of a depleted copper mine: (1) amending with a mixture of a technosol made of wastes and biochar and (2) amending combined with planting vegetation (Brassica juncea). Materials and methods A 3-month greenhouse experiment was carried out to evaluate the effects of orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The structures of the manure and biochar are suitable for improving soil fertility, as their pores offer increased surface area, nutrition, and moisture retention and can act as beneficial sites for soil microorganisms, while their anionic surfaces can increase the CEC for the retention of positively charged elements ( Mohamed et al., 2017 ; Edenborn et al., 2015 ; Ahmad et al., 2014 ). Furthermore, acacia wood-derived biochar has a high surface area and porosity, which would aid the adsorption of heavy metals ( Rodríguez-Vila et al., 2016 ; Fellet et al., 2014 ). From the SEM-EDS analysis, the biochar surface had a higher composition of carbon and oxygen than that of the manure ( Figure 1 c, d).…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the manure and biochar are suitable for improving soil fertility, as their pores offer increased surface area, nutrition, and moisture retention and can act as beneficial sites for soil microorganisms, while their anionic surfaces can increase the CEC for the retention of positively charged elements ( Mohamed et al., 2017 ; Edenborn et al., 2015 ; Ahmad et al., 2014 ). Furthermore, acacia wood-derived biochar has a high surface area and porosity, which would aid the adsorption of heavy metals ( Rodríguez-Vila et al., 2016 ; Fellet et al., 2014 ). From the SEM-EDS analysis, the biochar surface had a higher composition of carbon and oxygen than that of the manure ( Figure 1 c, d).…”
Section: Resultsmentioning
confidence: 99%
“…The neutral pH (6.8-7.2) and higher organic carbon content in the CP uppermost soil can decrease the availability of metals (Zn, Pb and Cd) and enhance plant growth to facilitate the phytostabilization process [57][58][59]. Moreover, other studies have also suggested that soil organic amendments can decrease metal availability by the formation of organic metallic complexes [60,61]. According to García-Carmona et al (2019a) and García et al ( 2009), pH appears to be the main property controlling Zn and Cd availability, increasing its solubility in acidic soil conditions [62,63].…”
Section: The Mineralogical Investigation Related To the Soil Propertiesmentioning
confidence: 99%
“…Although the authors applied much higher biochar doses than others (20, 40 and 80% wt. ), they found that Zn concentrations in the soil mobile fractions and in the plant Brassica juncea L., were generally higher in the biochar-amended soils compared to the untreated soils, suggesting than Zn was added by biochar itself [193,194]. Chao et al (2018) further elaborated on the phyto-availability of Zn by applying peanut shell biochar (1-5% wt.…”
Section: Znmentioning
confidence: 99%